(untitled) (Research, Society and Development, 2022)
The COVID-19 Pandemic caused several impacts around the world and in March 2020, due to the speed at which the virus spread across the continents, the social distancing policy was created to try to contain the advance, responsible for the interruption of numerous activities, including face-to-face classes. Thus, the search for remote teaching means was expanded, in order to alleviate the damage caused in education. The study has as general objective to analyze the obstacles in the use of remote learning for nursing students during the COVID-19 pandemic. This is bibliographic research of the integrative literature review type. Seven articles were included in this review, most of which presented a qualitative approach to data (71.4%). The CINAHL database provided the largest number of studies (71.4%). All articles focused on the year 2021 and were in English (100%); in which the United States and Nepal were the countries with the highest number of publications, with 28.6% each. The journal Nurse Education Today provided the greatest amount of evidence (28.6%). Regarding the research design, all studies were cross-sectional (100%), where all represented evidence level six. The pandemic affected the way knowledge is transferred, and made it difficult for students to carry out practical classes, where remote learning has become the safest and most effective alternative, using various online platforms, such as Zoom, Google Meet and Teams.